Push-out bond strength of four different Post systems: An in vitro study - Sanjeev Srivastava; Summaiyya Zaman Khan; Harpreet Chhabra; Sandeep Dubey; Arohan Singh; Kshiti Bhardwaj (Wolters Kluwer Medknow Publications, 2019)
Introduction: Endodontically treated teeth in most cases are left with the extensive loss of coronal tooth structure; hence, the salvaging of such teeth requires the use of an "intracanal retainer" such as post. The long-term success of any restorative or prosthetic rehabilitation of endodontically treated teeth depends on the quality of the restoration, clinical adaptation, and on the health of the supporting tissues. Materials and Methods: A total of 60 maxillary central incisors teeth were endodontically treated and Post space was prepared. The obturated teeth were randomly divided into four groups as follows: custom-made cast metal post, biological post, everstick post, and biological post. The consecutive posts were luted in each sample and sections were made. Push-out test was performed. The values were noted at bond failure and were subjected to statistical analysis. Results: Custom-made cast metal post showed the highest bond strength followed by prefabricated and everstick post. The least push-out bond strength was shown by prefabricated fiber post. Conclusions: The push-out values differed significantly according to posts systems used custom-made cast metal post showed the highest and prefabricated fiber post the least.